Kausalitas Pengeluaran Pemerintah, Inflasi, dan Pendapatan Nasional di Indonesia - Wildan Shohabi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This paper examines causality between government spending, inflation, and economic growth in Indonesia on bivariate framework for the period 1963 - 2013. This study uses Granger causality test to determine the short-term causality and Error Correction Model (ECM) methods by adding a dummy variable for economic and politic crisis to determine the long-term causality. The results showed that short-term bidirectional causality exist between inflation - government spending and inflation - national income, as well as unidirectional causality from government spending to national income. While in the case of long-term, bidirectional causality exist between government expenditure - national income and government expenditure - inflation, as well as unidirectional causality from national income to inflation. Policy implications for the government is focusing government spending to boost the national income and also considering its effect on inflation. Keywords: Government Spending, Inflation, National Income, Granger Causality, Error Correction Model.